Factors affecting consumer's selection of laundry detergents - Vergel, Michaela C.; Elumba, Patricia Santos (2005.)
Detergent manufacturers provide consumers a variety of laundry detergents with which to choose from for their laundering needs. Consumers select based on some considerations and there are factors that affect their selection. The study determined how consumers choose from the various laundry detergent variants available in the local market today. A focus group discussion was conducted on five (5) randomly selected respondents from Brgy. Krus na Ligas in the University of the Philippines, Diliman Community. The focus group discussion was a basis for formulating the survey questionnaire. Shoppers of UP Consumers Cooperative, Residents of Area 2 were the subjects of the survey. Convenience-purposive sampling was used within an eight (8)-day period. A total of 40 respondents (out of approximately 70 approached), which is 8% of the total population of the area or 20% of the total shoppers of UP Consumers' Cooperative in a day, answered the questionnaire. Content analysis was used to treat the data gathered from the focus group discussion; frequency distribution and percentage analysis were used to treat the data gathered from the survey questionnaire. Results showed that despite the many laundry detergent variants available in the market today and their different features, consumers choose laundry detergents that offer benefits to the garment. Factors that affect their selection of laundry detergents are the type of garment to be laundered, mass media, and selection determinants (e.g. price, smell and proven effectiveness of the laundry detergent). It was also noted that consumers are aware of the differences between various laundry detergent variants' properties through the information provided by media but the laundry detergents' benefits to the garments are known through actual experience or trying the laundry detergent variants for themselves. It is recommended that further studies concerning consumers' understanding of the information found in laundry detergent labels and their effects to different types of fabrics be conducted.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Consumer -- Attitudes; Detergents